fine needle aspiration cytology and ultrasonography in the management of solitary thyroid nodule - Al-Obaidi, Safa M.; Tajer, salah M.; ALnaffakh, hassan A.; Jouda, mohammed A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: the incidencies of clinically palpable thyroide nodules are 4% to 7%